Reviewing of Islamic Law on the Practice of Lending Money Through Mobile Banks - Wahyudin Wahyudin (Sekolah Tinggi Ilmu Bahasa Arab Darul Ulum Banyuanyar Pamekasan, 2022)
Borrowing money through Mobile Bank in people's lives is still common. This is because the needs are getting more urgent but the producers are not directly proportional to the income. For some people who are in a race between needs and income, borrowing money from a mobile bank is one solution, because the mobile bank offers an easy disbursement system. Therefore, this study reveals the Islamic view of the practice of lending money through mobile banks through a qualitative approach.